Analysis of Changes in Heat Exchange Properties of Charge Air Coolers in Automotive Vehicles’ Operation - Dmitry A. Dryuchin; Alexander D. Mikhailov (Вестник СибАДИ, 2025)
Introduction. A steady trend in the development of automobile engines’ designs was defined, which involves the widespread use of superchargers and coolers of the supplied air, providing the increase in technical, economic and environmental performance characteristics of motor vehicles. An urgent problem of efficiency reduction of the charge air coolers, due to the formation of impurities on both the outer and inner surfaces in operation was described. The results of scientific papers’ review in the field of improving the operation efficiency of automotive heat exchangers were presented. The purpose of the scientific work was formulated, the list of tasks to be solved was defined.Materials and methods. The theoretical statements describing the parameters of heat exchange processes at the boundary of two environments separated by a multilayer wall were presented. Calculation formulas have been determined allowing to define the influence nature of thermal conductivity and the thickness of contaminant layers on the surfaces of the heat exchange device on the volume of heat flow discharged by this device into the environment. A hypothesis has been put forward about the formation character of contaminant layers and about the existing value of their maximum thickness corresponding to the minimum of operational thermal conductivity. Methods of conducting experimental research and diagnostic equipment that ensures research performance aimed at obtaining the data necessary for the practical implementation of the developed theoretical statements were described.Results. The dependences of the thickness of the contaminant layers formed on the outer and inner surfaces of the charge air cooler in operation are given. The values of the thermal conductivity coefficients of outer and inner contaminants have been established, which is one of the points of scientific novelty. The obtained values were used to model the processes of heat removal from charge air and to develop measures aimed at improving the efficiency of vehicle operation. The article presents the results of modeling the heat flow discharged from the charge air and provides recommendations for enhancing the operation capacity of turbocharged engines.Discussion and conclusion. The solution of the determined goals was presented, the indicators reflecting the achievement of the research objective were defined, the results reflecting the new scientific accomplishments in the study were obtained. A brief description of practical recommendations aimed at improving the operation efficiency of turbocharged diesel engines was given.